The language attitude of border peoples Insular Riau, West Kalimantan, East Kalimantan, North Sulawesi, and the Eastern Sunda Islands - Sugono, Dendy; Utomo, Imam Budi; Hardaniwati, Menuk; Subiyatningsih, Foriyani (UI Scholars Hub, 2011)
This research aims at describing (1) the language use of border area societies (Insular Riau, West Kalimantan, East Kalimantan, North Sulawesi, and the Eastern Sunda Islands) in terms of local language (BD), Indonesian (BI), and foreign language (BA) in the domains of family, society, and occupation, (2) language activity of border area societies relating to news observation, language attention, and language constraints in mass media, (3) language attitude of border area societies towards BD, BI, and BA. The findings are as follows. First, within the family and society at large, BD is more frequently used than BI and BA. This shows that BD functions in non-formal situations. In the professional field, however, BI is more frequently used than BD. Second, people in border provinces widely observe mass media, whether printed or electronic. They also often pay attention to the language the mass media uses. Third, border societies have a positive attitude towards BD as is shown (agree/totally agree) by the answers to eight questions relating to BD. The language attitude of border societies towards BI is positive based on the answers (agree/totally agree) to seven questions concerning BI. This also means that BI is prestigious for border people, especially in formal communication. The language attitude of border societies towards BA is mixed. In as far as it is negative it implies a positive evaluation of BD and BI because people appreciate them as part of their local and national identities.